A Stakeholder Rationale for Risk Management Implications for Corporate Finance Decisions - Gossy, Gregor (Gabler Verlag : Imprint: Gabler Verlag, 2008)
Ordinarily, only the interests of shareholders, debtholders, and corporate management are taken into account when analyzing corporate financial decisions while the interests of non-financial stakeholders are often neglected. Gregor Gossy develops a so-called stakeholder rationale for risk management arguing that firms which are more dependent on implicit claims from their non-financial stakeholders, such as customers, suppliers, and employees, prefer conservative financial policies. In order to perform panel data analyses of the determinants of corporate financial decisions, the author uses data from Austrian and German industrial companies. He shows that variables for a firm's most important non-financial stakeholders explain the firm's capital structure and cash holding decisions. His findings suggest that a firm's choice of accounting standards have a moderating effect on the determinants of corporate finance decisions.